STRATEGI DIGITAL MARKETING DAN PEMBAYARAN DIGITAL SEBAGAI UPAYA PENGUATAN UMKM DI PASAR TRADISIONAL JAKARTA - Novel Syahputra; Ivan Crespo; Mesra Dinda Telaumbanua; Anita Yulianti Sinaga (CV. Denasya Smart Publisher, 2026)
Advances in digital technology have triggered a major transformation in marketing practices and transaction mechanisms, particularly for Micro, Small, and Medium Enterprises (MSMEs) in traditional markets in Jakarta. However, a lack of understanding of digital technology, limited access to technology, and conventional business models remain major obstacles to improving the competitiveness of MSMEs. This study aims to examine the contribution of digital marketing strategies and digital payment systems as measures to strengthen MSMEs in Jakarta's traditional markets. The research approach applied is a descriptive qualitative method, with data collection through observation, interviews, and literature review. The findings reveal that the application of digital marketing through social media platforms, e-commerce sites, and instant messaging applications can increase product exposure, expand market coverage, and strengthen customer relationships. In addition, the adoption of digital payment systems such as electronic wallets and QRIS facilitates transactions, increases operational efficiency, and encourages financial participation for MSME players. However, the implementation of this strategy still faces obstacles, such as limited human resources and supporting infrastructure. Therefore, collaboration between the government, market managers, and MSME players is needed through training programs, mentoring, and the provision of digital facilities for the digital transformation of MSMEs.